EFFECT OF SHIELDING GAS ON THE PROPERTIES OF STAINLESS-STEEL SUS 304L PLUG WELDED - Ilham Habibi; Januar Tri Prasetyo; Nurul Muhayat; Triyono Triyono (Jurnal Rekayasa Mesin, 2022)
The effect of shielding gas composition and welding current on the mechanical-physical properties of plug welding joint stainless steel SUS 304L has been investigated. Metal Inert Gas (MIG) welding was used to join SUS304L with a thickness of 3 mm. The variations of welding current were 80 A, 100 A, and 120 A, while variations of shielding gas composition were 100% Ar; 92,5% Ar-7,5% CO2; 85% Ar-15% CO2; 77,5% Ar-22,5% CO2; 100% CO2. Macro and microstructural tests were conducted to determine welded joints physical properties. Tensile-shear testing and micro hardness Vickers were done to determine welded joints physical properties. The results show that the higher level of welding current and CO2 content in the shielding gas, the more tensile-shear load bearing capacity and decreased hardness. The welding current of 120 A and shielding gas 77,5% Ar-22,5% CO2 produced welded joints with the highest tensile-shear load bearing capacity. The nugget size increased as the higher level of welding current and the CO2 content in the shielding gas due to the increase of heat input.